Fast Screening of Tyrosinase Inhibitors in Coreopsis tinctoria Nutt. by Ligand Fishing Based on Paper-Immobilized Tyrosinase - Ayzohra Ablat; Ming-Jie Li; Xiao-Rui Zhai; Yuan Wang; Xiao-Lin Bai; Peng Shu; Xun Liao (Molecules, 2024)
Coreopsis tinctoria Nutt. is an important medicinal plant in traditional Uyghur medicine. The skin-lightening potential of the flower has been recognized recently; however, the active compounds responsible for that are not clear. In this work, tyrosinase, a target protein for regulating melanin synthesis, was immobilized on the Whatman paper for the first time to screen skin-lightening compounds present in the flower. Quercetagetin-7-O-glucoside (1), marein (2), and okanin (3) were found to be the enzyme inhibitors. The IC50 values of quercetagetin-7-O-glucoside (1) and okanin (3) were 79.06 ± 1.08 μM and 30.25 ± 1.11 μM, respectively, which is smaller than 100.21 ± 0.11 μM of the positive control kojic acid. Enzyme kinetic analysis and molecular docking were carried out to investigate their inhibition mechanism. Although marein (2) showed a weak inhibition effect in vitro, it inhibited the intracellular tyrosinase activity and diminished melanin production in melanoma B16 cells as did the other two inhibitors. The paper-based ligand fishing method developed in this work makes it effective to quickly screen tyrosinase inhibitors from natural products. This is the first report on the tyrosinase inhibitory effect of those three compounds, showing the promising potential of Coreopsis tinctoria for the development of herbal skin-lightening products.